Poly-2-isopropyl-2-oxazoline: conformational characteristics, LCST behavior and complexation with curcumin - Kirila, T Yu; Kozina, N D; Golovina, M A; Sokolova, M P; Tenkovtsev, A V; Filippov, A P (Soft matter, 2025)
A homologous series of thermoresponsive poly-2-isopropyl-2-oxazolines were synthesized using living cationic ring-opening polymerization. The molar mass and hydrodynamic characteristics of poly-2-isopropyl-2-oxazolines were determined using methods of molecular hydrodynamics and optics in dilute ethanol solutions. The molar masses of the samples varied almost tenfold (2600-22 100 g mol ). For poly-2-isopropyl-2-oxazolines, the exponents in the Kuhn-Mark-Houwink-Sakurada equations for intrinsic viscosity (0.54) and translational friction coefficient (0.53) were typical for flexible-chain polymers. The equilibrium rigidity of poly-2-isopropyl-2-oxazolines (Kuhn segment length was 2.0 nm) was determined by analyzing the hydrodynamic characteristics using theories that take into account volume effects in thermodynamically good solvents. It was shown that the rigidity of poly-2-alkyl-2-oxazolines increases with the growth of the size of the side radical, even when the carbon atom number in the latter is not large. In aqueous solutions, poly-2-isopropyl-2-oxazolines exhibited LCST behavior. Phase separation temperature and LCST decreased with increasing molar mass due to the growth of polymer hydrophobicity. The highly efficient binding of curcumin by poly-2-isopropyl-2-oxazoline in aqueous solutions was observed. Stable complexes of poly-2-isopropyl-2-oxazolines with curcumin were formed in water. Solutions of complexes were thermoresponsive, and the addition of curcumin did not change the phase separation temperature since the curcumin content was very low.